2012
DOI: 10.4322/natcon.2012.009
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Migratory Birds in the Expansion of Araucaria Forest

Abstract: The present study assessed the variation in bird species composition, and in the proportion of frugivorous and migratory individuals between areas of continuous forest and patches of Araucaria forests in natural grassland areas of southern Brazil. In the grassland-forest mosaic, 703 individuals of 83 bird species were recorded. The proportion of frugivorous and migratory individuals was significantly higher in forest patches and in the interior of continuous forest, compared to forest edges. We suggest that mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The elevated species richness of the family Tyrannidae is directly related to the variation observed in the seasonality, because this group corresponds to one third of the austral migrants [48], with preference for open areas [49]. The seasonal variation found for the parameters of diversity has practical implications for ecological restoration, as some studies have indicated a direct relationship between the presence of migratory species and a seasonal increase in the deposition of seeds dispersed by birds [50][51].…”
Section: Discussionmentioning
confidence: 99%
“…The elevated species richness of the family Tyrannidae is directly related to the variation observed in the seasonality, because this group corresponds to one third of the austral migrants [48], with preference for open areas [49]. The seasonal variation found for the parameters of diversity has practical implications for ecological restoration, as some studies have indicated a direct relationship between the presence of migratory species and a seasonal increase in the deposition of seeds dispersed by birds [50][51].…”
Section: Discussionmentioning
confidence: 99%
“…This synchrony between peak fruit availability and peak disperser abundance in this agroecosystem emphasizes the importance of this mutualism (Zanini & Ganade 2005, Jordano et al 2006, Carlo et al 2007, Hartz et al 2012. In summary, we found seasonal variation in the richness and abundance of the avian fauna using the artificial perches in the early stages of forest regeneration (B2 years of age) within a restoration experiment.…”
Section: Effectmentioning
confidence: 76%
“…Thus, seasonal matching between perch use by dispersers and the phenological cycle of vegetation is key to the effectiveness of perches in promoting the dispersal of forest seeds (Zanini & Ganade 2005). Little attention has been given to the relationship between annual variation in the deposition of seeds and the resulting changes in the composition of the bird assemblage (Vicente et al 2010, Hartz et al 2012. For example, one-third of the austral migrants are the Tyrannidae family (Chesser 1994, Alves 2007 and their strong preference for perches (Holl et al 1998, Vicente et al 2010 and migratory behavior could be reflected in the seasonal changes in the use of artificial perches.…”
Section: Introductionmentioning
confidence: 99%
“…1B-E). They produce large seeds that are heavily consumed and dispersed by an array of birds and mammals (Hartz et al 2012). Despite their ability to withstand shade as seedlings (Duarte and Dillenburg 2000), they have D r a f t 8 been shown to be long-lived pioneers that require extensive canopy openings to reach maturity and whose abundance is negatively related to the abundance of angiosperm trees (Souza 2007, Souza et al 2008, 2014.…”
Section: Study Area and Speciesmentioning
confidence: 99%